PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA MATERI BAGIAN TUBUH TUMBUHAN DAN FUNGSINYA KELAS IV SEKOLAH DASAR - Silvika, Silvika; Ardiansah, Feri; Pitriyana , Sisi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The author's research was motivated by the lack of media integration in the teaching and learning process, particularly in science education, where teachers use textbooks and pedagogical models that are oriented towards educators. The research aimed to develop augmented reality media that is valid, practical, and effective in teaching fourth-grade elementary school students about plant parts and their functions. The research used Research and Development (R&D) through the use of the ADDIE development model, which includes five processes: Analyze, Design, Development, Implementation, and Evaluation. The author's study involved 26 fourth-grade students, covering both small and large scales. The method applied to collect data was a test questionnaire. The data analysis methodology used was qualitative descriptive analysis and quantitative descriptive analysis. Practicality data was obtained from the results of student response questionnaires. The effectiveness data was obtained from the analysis of the pretest and posttest scores. The validation results from two media experts were both 90%, which is classified as “Highly Valid.” On the other hand, the validation results from two subject matter experts were 80% and 87.5%, respectively, which is classified as “Valid.” The average percentage of pretest and posttest questions reached 85%, which is classified as “Valid.” The practicality level of augmented reality learning media in the limited-scale product trial stage reached 100%, classified as “Very Practical.” Meanwhile, in the large-scale product trial stage.